“I was like an alien”: Exploring how Indigenous students succeed in university studies - King, Alyson E.; Brigham, Susan M. (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur, 2022)
This article explores the strategies used by Indigenous students attending three Canadian universities (in Nova Scotia, Ontario, and Manitoba) to find success in their studies. As part of a larger study on the success strategies of students who have been traditionally underrepresented in Canadian universities, this article draws on the responses of students who self-identify as Indigenous and insights from a key informant. We argue that the voices of Indigenous students are essential in the processes of institutional decolonizing and reconciliation and of reimagining universities as inclusive, equitable spaces for Indigenous students and their academic success